Binding Force Analysis and Simulation Experiment of Forcing Pairs of Three Pairs Bars Space RCCR Mechanism - Cui Chao; Zhuang Sen (Jixie chuandong)
It is difficult to solve the binding force of motion pairs of over-constrained mechanisms. This study attempted to decompose the constraint term in the d'Alembert principle into two parts, static constraint and dynamic constraint. The static constraint under constraint conditions and the dynamic constraint of the equilibrium inertial force were obtained separately, and the total constraint force of the example was solved through the superposition of the two. Taking three pairs of uniform transmission rod space RCCR mechanism as the research object, the binding force was solved by the above method, and the solution results were compared with the dynamic simulation results. The results show a good consistency.